Intrainstitutional Changes of the Treatment of Supracondylar Humerus Fracture in Children over a Period of 9 Years - Ferdinand Wagner; Amalia Boeriu; Pascal Eberz; Annabelle Weigert; Boris Michael Holzapfel; Wolfgang Böcker; Jochen Hubertus; Oliver Muensterer; Florian Bergmann; Christian Max Ziegler (MDPI AG, 2023)
To assess changes in treatment modalities for supracondylar humerus fractures (SCHFs) at a large pediatric university hospital, we analyzed patient data from 2014 to 2022. A total of 233 SCHFs treated surgically at our hospital were included. To evaluate postoperative outcome and quality of life, DASH and EuroQol-5D-Y questionnaires were sent to patients. In addition to a significant fluctuation in fracture severity, we found an increase in training interventions (more surgeries were performed by trainees) and a significant decrease in surgery times after 2016. From 2020, there was a significant shift in the type of surgical method away from closed reduction with elastic stable intramedullary nailing (ESIN) and towards closed reduction and crossed K-wire osteosynthesis (CRK). Surgeries performed in the morning and evening hours increased, while those performed in the afternoon and after midnight decreased. After a mean follow-up of 4 years, there was no difference in elbow function between ESIN and open reduction and K-wires (ORK). Treatment with ESIN was equivalent to ORK in terms of function, at least in the medium-term follow-up. In summary, the combination of shifting treatment from SCHF to daytime hours, increasing trainee participation and using cross K-wire fixation instead of ESIN had no negative impact on surgery times. In our setting, these measures have reduced resource utilization and increased efficiency without compromising patient care.